Efficacy and tolerability of preoperative chemoradiotherapy with S-1 alone for locally advanced rectal cancer. (21st December 2020) - Imano, Nobuki; Murakami, Yuji; Kubo, Katsumaro; Kawahara, Daisuke; Takeuchi, Yuki; Nishibuchi, Ikuno; Kimura, Tomoki; Kochi, Masatoshi; Takakura, Yuji; Shimizu, Wataru; Egi, Hiroyuki; Uegami, Shinnosuke; et al.
Abstract: Preoperative chemoradiotherapy with capecitabine or 5-fluorouracil is a standard treatment for locally advanced rectal cancer (LARC). S-1, a prodrug of 5-fluorouracil, is a candidate for this chemoradiotherapy regimen in Japan; however, treatment outcomes after S-1 treatment alone are not clear. This study aimed to assess the efficacy and tolerability of preoperative chemoradiotherapy with S-1 alone for LARC. We retrospectively evaluated 54 LARC patients who underwent preoperative chemoradiotherapy with S-1 alone in our institution between 2005 and 2017. The clinical tumor stage was cT2–3 in 31 patients and cT4 in 23 patients, and lymph node metastases were clinically evident in 31 patients. S-1, at a dose of 80 mg/m 2 /day, was orally administered during radiotherapy. A total dose of 45–50.4 Gy was delivered in 25–28 fractions (median: 50.4 Gy). Surgical resections were scheduled 6–10 weeks after chemoradiotherapy completion. The 3- and 5-year overall survival rates were 92.4 and 72.8%, respectively, with a median follow-up time of 51 months. The 3- and 5-year local control rates were 96.2 and 85.9%, respectively. A pathological complete response was observed in 7 patients (13.0%) at the time of surgery. Ten patients (18.5%) had grade 3 acute toxicities and 5 patients (9.3%) had grade 3 late toxicities. No grade 4 or 5 toxicities were observed. Preoperative chemoradiotherapy with S-1 alone followed by total mesorectal excision resulted in a low incidence of toxicities and comparable clinical results. Therefore, S-1 alone can be a treatment option for preoperative chemoradiotherapy in LARC patients.